Tinjauan Penentuan Pajak Terutang PPh 21 Pada Aparatur Sipil Negara BKPSDM Kab.Gowa - Amran, Amran; Pratiwi, Putri Ayulia; Masrullah, Masrullah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
Income tax (PPh) Article 21 payable is tax payable calculated from taxable income (PKP) in a year minus non-taxable income (PTKP). Where the imposition of PPh in Indonesia is implemented progressively. The object of this research is BKPSDM Gowa Regency. The purpose of this study was to find out whether the determination of the tax payable PPH 21 on the state civil apparatus BKPSDM Gowa Regency is in accordance with Law No. 36 of 2008. Data collection was carried out using interviews and documentation techniques. The analysis technique used is descriptive qualitative analysis. The results of this study indicate that BKPSDM Kab. Gowa has complied with laws and regulations regarding pph 21 which are regulated in Law No. 36 of 2008 concerning income tax.